National Education Policy 2020: Opportunities & Challenges - APV Appa Rao; L Malleswara Rao; P Ramakrishna Rao (AG Volumes, 2024)
The nation of India continues to lead the international community in terms of economic development, equality, social justice, and national progress as a result of its consistent efforts to provide higher quality education to all. The Government of India’s initial education policy for the twenty-first century is the "National Education Policy" (NEP), 2020. It aims to satisfy the nation’s numerous, rapidly expanding development needs. The National Education Policy 2020 serves as a comprehensive framework that aims to revolutionise the education system in India by effectively tackling the emerging requirements and challenges of the nation’s educational landscape. The policy incorporates a range of reforms and initiatives that seek to foster equitable access to high-quality education, equitable development, and a student-centered approach. It envisions a transition to a more comprehensive and adaptable education system that prioritises the development of skills, critical thinking, and creativity. Additionally, it emphasises the integration of technology, the encouragement of multidisciplinary learning, and the cultivation of an environment that fosters innovation and research. In its entirety, the National Education Policy 2020 delineates a comprehensive and audacious blueprint for the advancement of education in India. However, the effective execution of this policy will necessitate the continued and collaborative engagement of all pertinent parties—policymakers, educators, students, and parents—in order to achieve success.